Evidence for BMP‐mediated specification of primordial germ cells in an indirect‐developing hemichordate. Issue 1 (1st December 2020) - Lin, Ching‐Yi; Yu, Jr‐Kai; Su, Yi‐Hsien
Abstract: Primordial germ cells (PGCs) are specified during development by either one of two major mechanisms, the preformation mode or the inductive mode. Because the inductive mode is widely employed by many bilaterians and early branching metazoan lineages, it has been postulated as an ancestral mechanism. However, among the deuterostome species that have been studied, invertebrate chordates use the preformation mode, while many vertebrate and echinoderm species are known to utilize an inductive mechanism, thus leaving the evolutionary history of PGC specification in the deuterostome lineage unclear. Hemichordates are the sister phylum of echinoderms, and together they form a clade called Ambulacraria that represents the closest group to the chordates. Thus, research in hemichordates is highly informative for resolving this issue. In this study, we investigate the developmental process of PGCs in an indirect‐developing hemichordate, Ptychodera flava . We show that maternal transcripts of the conserved germline markers vasa, nanos, and piwi1 are ubiquitously distributed in early P. flava embryos, and these genes are coexpressed specifically in the dorsal hindgut starting from the gastrula stage. Immunostaining revealed that Vasa protein is concentrated toward the vegetal pole in early P. flava embryos, and it is restricted to cells in the dorsal hindgut of gastrulae and newly hatched larvae. The Vasa‐positive cells later contribute to the developing trunk coeloms of the larvae and eventually reside in the adult gonads. We further show that bone morphogenetic protein (BMP) signaling is required to activate expression of the germline determinants in the gastrula hindgut, suggesting that PGC specification is induced by BMP signaling in P. flava . Our data support the hypothesis that the inductive mode is a conserved mechanism in Ambulacraria, which might even trace back to the common ancestor of Deuterostomes. Abstract : Schematic summary of Vasa protein, vasa mRNA, and nanos mRNA distributions during development of invertebrate deuterostomes. In this study, we investigate the developmental process of PGCs in an indirect‐developing hemichordate, Ptychodera flava. We show that maternal transcripts of the conserved germline markers vasa, nanos, and piwi1 are ubiquitously distributed in early P. flava embryos, and these genes are co‐expressed specifically in the dorsal hindgut starting from the gastrula stage. We also show that BMP signaling is required to activate expression of the germline determinants in the gastrula hindgut, suggesting that PGC specification is induced by BMP signaling in P. flava. Our comparative analysis further suggests that this induction mode may represent an ancestral feature of Ambulacraria, which may even date back to the common ancestor of Deuterostomes. Research Highlights: Germline markers are coexpressed in the dorsal hindgut of the hemichordate embryo. Vasa‐positive cells contribute to the larval trunk coeloms and subsequently to the gonads. Bone morphogenetic protein signaling is required for the expression of germline markers.